510. Reduced Mortality Rate in Critically Ill Patients with COVID-19 with the Implementation of a Treatment Protocol—Experience of a Tertiary Care Center in the Midwest During the Initial Surge of COVID-19. (4th December 2021) - Kaushik, Ashlesha; Gupta, Sandeep; Gupta, Jitendra
Abstract: Background: COVID-19 has been an unprecedented pandemic resulting in high mortality. We report our experience of using a treatment protocol in the intensive care unit (ICU) during the first peak of the pandemic. Methods: All patients diagnosed with SARS-CoV-2 infection admitted to the ICU between April 14-June 14, 2020 were included. Remdesivir was made available for use in our institution on May 14 th 2020, and thereafter, a treatment protocol combining remdesivir, corticosteroids and tocilizumab was implemented in the ICU, with doses as follows: Remdesivir 200mg intravenously (I.V.) on day 1, then 100 mg for 4 days; tocilizumab 400 mg I.V. once a day for 2 days; dexamethasone 6 mg I.V. daily for 10 days followed by taper. During pre-protocol period, patients were receiving hydroxychloroquine (400 mg once on day 1 followed by 200 mg twice daily orally for 4 days). We compared the pre-protocol period (labeled as P1: April 14, 2020- May 13, 2020) with protocol period (P2: May 14, 2020 -June 14, 2020) for clinical outcomes. Results: A total of 32 and 48 patients were included during P1 and P2 respectively. Both groups were similar in terms of demographic characteristics, mean (±SD) age [55(±10) and 54 (±12) years] and mean Charlson-Deyo risk score at admission [2.4(±0.8) and 2.5 (±0.9) respectively]. During both periods, a comparable number of patients needed mechanical ventilation (65% and 66% respectively), anticoagulation (74% and 76% respectively) and inotropes (41% and 40%). The mean duration of ICU stay during P1 was significantly longer than P2 [15.4 (±2.8) days versus 9.3 ± (3.8) days, p< 0.0001)]. During P1, mean duration of mechanical ventilation [10 (±1.6) days] was also significantly longer than P2 [7.1 (±2.7) days] (p= 0.0004). There was a significant reduction in mortality rate from 68% (22/32) during P1 to 10.4% (5/48) in P2 (p< 0.0001). Patients were 4.3 times more likely to die during P1 than P2 (95% CI= 2.47-7.86). Conclusion: Our results showed a decrease in ICU mortality rate by 57.6% with the implementation of a treatment protocol combining remdesivir, tocilizumab and corticosteroids during the first months of the initial surge of the pandemic, with a significant decline in length of ICU stay and duration of mechanical ventilation; and support the therapeutic data endorsed by IDSA/NIH guidelines. Disclosures: All Authors : No reported disclosures